Technical Note on Root Coverage of Lower Anterior Teeth Using a Partially Deepithelialized Connective Tissue Graft (PE-CTG) Aided by a High-Speed Handpiece - Kyeong-Ok Lim; Byung-Ock Kim; Won-Pyo Lee (Hindawi Limited, 2020)
Root coverage in the mandibular anterior region is challenging because of a thin gingival biotype, shallow vestibule, and high frenum attachment. Several methods have been introduced to predict the root coverage in this area. Stimmelmayr proposed a method of performing root coverage using a combination epithelialized-subepithelial connective tissue graft (CTG). However, it is difficult to precisely acquire connective tissue according to this method. Therefore, in this case report, we would like to introduce a technique to harvest a partially deepithelialized CTG (PE-CTG) aided by a high-speed handpiece, which helps in procuring the graft easily and quickly. This method could lower the patient's morbidity at donor sites and enhance the healing process. Additionally, it could increase the amount of keratinized gingiva in the mandibular anterior region without reducing the vestibular depth. Therefore, PE-CTG using a high-speed handpiece can be a promising treatment option for the root coverage of the mandibular anterior teeth.